The Influence of Previous Audit Opinion, Audit Tenure and Liquidity toward Going Concern Opinion in Manufacturing Companies for the Period of 2015-2017 - Cindy Saputra Kuswara; Ery Yanto (JAAF (Journal of Applied Accounting and Finance), 2019)
Going Concern Opinion issued by auditor when there is doubt of a company’s ability to continue as going concern. This research have the objective to determine the relationship between Previous Audit Opinion, Audit Tenure and Liquidity with Going Concern Opinion in manufacturing companies listed in IDX form years 2015 until 2017. The population of this research is 156 with total of sample are 37 manufacturing companies. The research of data using descriptive statistic and logistic regression analysis method. The result shows that Previous Audit Opinion and Liquidity have significant influence toward Going Concern Opinion and Audit Tenure does not have significant influence toward Going Concern Opinion.